The experimental model of bone marrow cells autotransplantation at local mechanical brain trauma - N. Ya. Gridina; O. V. Serkiz; A. M. Zolotoverkh; A. A. Nakhaba; O. N. Velichko; O. I. Veselova (Ukrainian Neurosurgical Journal, 2010)
The model of bone marrow cells autotransplantation in area of brain trauma of rats that can be used for morphological, biochemical, behavioral and other researches providing on laboratory animals is submitted. The actuality of experimental model creation consists in opportunity of a lifetime fence of bone marrow cells and their transplantation into brain damaged areas without previous cultivation.